Terpaan Media Sosial dalam Minat Fashion dan Kepercayaan Diri Remaja - Mulyadi, Septian; Silvana, Hana (Gunahumas, 2022)
Confidence is currently a problem that is often experienced by teenagers, especially when using social media. Even according to psychologists, social media at this time is one of the triggering factors for the crisis of self-confidence in adolescents. But on the other hand, the use of social media is a necessity to obtain sources of information, one of which is about fashion content. One of the social media that is often used by teenagers today is Twitter. Twitter is popular because of the auto base feature that can send tweets anonymously. This study was conducted to prove whether individuals who have an interest in fashion will be affected by their self-confidence by being exposed to the @ustadchen Twitter account. In assisting the research, a quantitative approach is used with the moderate regression method. The participants in this study were 383 active followers of the @ustadchen Twitter account by filling out a statement questionnaire. The results showed that interest in fashion with indicators of interest, attention, and desire had a positive and significant effect on adolescent self-confidence. In addition, media exposure with indicators of frequency, duration, and attention strengthens the influence of fashion interest on adolescent self-confidence. This shows that the higher the media exposure of the @ustadchen Twitter account, the influence of fashion interest on adolescent self-confidence increases. Based on the results of the study, interest in fashion and media exposure affects adolescent confidence in the positive and significant categories, so in this case, social media plays a role in building adolescent confidence.